Writing persuasive texts: Using grammatical metaphors for rhetorical purposes in an educational context. Issue 2 (2nd April 2020) - To, Vinh; Thomas, Damon; Thomas, Angela
ABSTRACT: Persuasive language has been described as the language of power. When a person can use persuasive language effectively in speech and writing, it increases their ability to participate and access power in democratic societies. Persuasive writing is one of three key text types in the Australian Curriculum: English, and language features of persuasive text types are taught across the curriculum. Australian students' ability to write persuasive texts has been assessed in seven of the past nine years of National Assessment Program – Literacy and Numeracy (NAPLAN) testing. One of the language features that is considered important in persuasive writing is grammatical metaphor. This paper employs concepts from systemic functional linguistics to examine how ideational grammatical metaphor was used in the 32 highest scoring persuasive texts written by Tasmanian primary and secondary school students for the 2011 NAPLAN test. The results show that high achieving students demonstrated an ability to use ideational metaphor in their persuasive writing from the middle primary school years. This paper aims to provide guidance for Australian primary and secondary school educators by showing how and in what ways high achieving students use grammatical metaphor for persuasive purposes in NAPLAN responses across the tested year levels.